1967
DOI: 10.1172/jci105615
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Factor-mediated Attachment of Vitamin B12 to Brush Borders and Microvillous Membranes of Hamster Intestine*

Abstract: Summary. Hamster intrinsic factor (IF) preparations markedly enhanced the uptake of 57cobalt-labeled cyanocobalamin (B_2-57Co) by brush borders and microvillous membranes isolated from villous absorptive cells obtained from the distal but not the proximal half of hamster intestine. A similar effect was observed with rat and rabbit IF preparations, but IF preparations obtained from man, dog, and hog were ineffective. After -fractionation of hamster IF preparations by gel filtration or ion exchange chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

1968
1968
1991
1991

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(45 citation statements)
references
References 19 publications
3
42
0
Order By: Relevance
“…Such a localization of this binding factor is consistent with the observations of Donaldson, Mackenzie, and Trier (28) that human gastric juice enhanced the uptake of B12 to epithelial cell brush borders and microvillous membranes of the distal small intestine of the hamster. Mackenzie, Kopp, Donaldson, and Trier (29) recently reported that antiserum produced against isolated brush border preparations inhibited the uptake of vitamin B1,.…”
Section: Resultssupporting
confidence: 90%
“…Such a localization of this binding factor is consistent with the observations of Donaldson, Mackenzie, and Trier (28) that human gastric juice enhanced the uptake of B12 to epithelial cell brush borders and microvillous membranes of the distal small intestine of the hamster. Mackenzie, Kopp, Donaldson, and Trier (29) recently reported that antiserum produced against isolated brush border preparations inhibited the uptake of vitamin B1,.…”
Section: Resultssupporting
confidence: 90%
“…The mechanism of IF-mediated B12 absorption is not well understood, but a number of studies have demonstrated that IF facilitates B12 binding to ileal sacs (1)(2)(3)(4)(5)(6), mucosal homogenates (4,(7)(8)(9)(10), microvillus membrane preparations (11,12), and to a component solubilized from ileal mucosa with Triton X-100 (13). IF-facilitated B12 binding of this type is dependent on pH, is inhibited by EDTA, and is postulated to represent the first step in the complex process by which B12 passes from the intestinal lumen into the portal blood.…”
Section: Introductionmentioning
confidence: 99%
“…IF-facilitated B12 binding of this type is dependent on pH, is inhibited by EDTA, and is postulated to represent the first step in the complex process by which B12 passes from the intestinal lumen into the portal blood. (2,7,9,11,14,15) or not (3,6,8,16) (17). Binding studies using crude gastric preparations are difficult to interpret because of the presence of B12 binding proteins that lack in vivo IF activity as well as the possible presence of additional gastric inhibitors or stimulators.…”
Section: Introductionmentioning
confidence: 99%
“…Non-IF B12-binders obtained from various animal tissues did not augment the B12 uptake by guinea pig IMH (25,44), isolated brush borders (33) and seg ments (52) of hamster small intestine.…”
Section: Discussionmentioning
confidence: 84%
“…The IMH took up B12 in the absence of either Ca2+ or Mg2+ almost equally well as in the complete system ( Table 2). The deletion of Ca2+ resulted in a reduction of uptake aug mented by IF, indicating that Ca2+ plays an important role in the uptake of B12 mediated by IF (3,(31)(32)(33)(34)(35)(36)(37)(38). In contrast to IF, the aug mentation by the B12-binding principle was not affected by the deletion of divalent cations.…”
mentioning
confidence: 94%